2020
DOI: 10.5114/aoms.2019.86928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidepressants on QT interval in people with mental disorders

Abstract: Introduction: Drug-induced QT prolongation is associated with higher cardiovascular mortality. Material and methods: We conducted a protocol-based comprehensive review of antidepressant-induced QT prolongation in people with mental disorders.Results: Based on findings from 47 published randomized controlled trials (RCTs), 3 unpublished RCTs, 14 observational studies, 662 case reports of torsades de pointes, and 168 cases of QT prolongation, we conclude that all antidepressants should be used only with licensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…The risk of QTc prolongation and associated tachyarrhythmia is likely to be greater in the elderly, in patients with cardiovascular and other co-morbidity and in those on other pharmacotherapy, especially polypharmacy (Franchi et al, 2016). It is suggested that all antidepressants may carry this risk and that therefore QTc and clinical symptoms of arrhythmia should be monitored for all antidepressants (Aronow and Shamliyan, 2020). There is debate regarding whether particular agents are more problematic in this regard.…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of QTc prolongation and associated tachyarrhythmia is likely to be greater in the elderly, in patients with cardiovascular and other co-morbidity and in those on other pharmacotherapy, especially polypharmacy (Franchi et al, 2016). It is suggested that all antidepressants may carry this risk and that therefore QTc and clinical symptoms of arrhythmia should be monitored for all antidepressants (Aronow and Shamliyan, 2020). There is debate regarding whether particular agents are more problematic in this regard.…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 99%
“…Among second generation antidepressants, it has been suggested that citalopram and escitalopram are differentially associated with QTc prolongation and arrhythmias (Qirjazi et al, 2016). However, it has been suggested that this risk exists also with other antidepressants (Aronow and Shamliyan, 2020). Where antidepressants are to be used in higher than standard doses in the elderly, baseline and steady state QTc monitoring is recommended.…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 99%
“…Antipsychotic and antiepileptic medications have been reported to have a range of cardiac side-effects, including orthostatic hypotension [ 43 ], cardiomyopathy [ 44 ], QT prolongation [ 45 ] and increased risk for SCD [ 9 ]. Moreover, antidepressant drugs have been associated with adverse cardiac effects: the selective serotonin reuptake inhibitors (SSRIs) and particularly the tricyclic antidepressants are known to cause prolongation of the heart rate corrected QT interval (QT c ) on an ECG and predispose to ventricular arrhythmias [ 46 , 47 ]. These cardiotoxic effects of psychiatric disorder therapeutics are of particular importance in patients with an underlying CVD.…”
Section: Psychiatric Disorders and Cardiovascular Diseasesmentioning
confidence: 99%
“…A systematic review of non-cardiac patients found observational low-quality studies reporting evidence of increased sudden death associated with higher doses of tricyclic anti-depressants and specific selective serotonin and norepinephrine reuptake inhibitors such as venlaxafine. In addition, they reported an increase in the risk of all-cause mortality in patients taking anti-depressants that prolong the QT interval [52]. HF patients are frequently prescribed anti-arrhythmics and are at risk of polypharmacy and of electrolyte disturbances, which may further increase the risk of potentially lethal arrhythmias in the setting of anti-depressant therapy.…”
Section: Discussionmentioning
confidence: 99%